Amy's view - Hare, David, 1947- (Faber and Faber, 1997)
Esme Allen is a well-known West End actress at just the moment when the West End is ceasing to offer actors a regular way of life. A generational play about the long term struggle between a strong mother and her loving daughter, Amy's View mixes love, death and the theatre in a way which is both heady and original